A basal sphenodontian (Lepidosauria) from the Jurassic of Patagonia: New insights on the phylogeny and biogeography of Gondwanan rhynchocephalians - Apesteguía, S. (2012)
Herein we describe a new rhynchocephalian taxon from the Middle Jurassic of Patagonia, Argentina, representing the first Jurassic record of the group in South America. The new taxon, consisting of a complete dentary, is ascribed to Sphenodontia based on the presence of a deep and wide Meckelian groove, long posterior process, well-developed coronoid process, and acrodont teeth showing dental regionalization including successional, alternate hatchling, and additional series. This allocation is reinforced by a phylogenetic analysis that places the new taxon in a basal position within a clade of sphenodontians that excludes Diphydontosaurus and Planocephalosaurus. Additionally, the new taxon clusters within a Gondwanan clade with the Indian Godavarisaurus from the Jurassic Kota Formation, sharing the presence of recurved and relatively large posterior successional teeth that are ribbed and bear a peculiar anterolingual groove. This sister-group relationship is intriguing from a palaeobiogeographical viewpoint, as it suggests some degree of endemism during the initial stages of the breakup of Pangaea. We also discuss the ontogenetic stage of the new taxon and provide insights on the evolution of successional dentition in rhynchocephalians. © 2012 The Linnean Society of London.